Crime and punishment in america - Currie, Elliott (New York: Henry Holt, 1998)
Contiene: Assessing the prision experiment, Prison myths. Alternatives I: prevention. Alternatives II: Social actionb. Alternatives III: The justice system. Conclusion: choices
Keywords: Punishment